Percutaneous nephrolithotomy. Presentation of a patient - Freddy Castillo Guerra; Jorge Cándido Monzón Rey; Raúl Santiago López Montes (Acta Médica del Centro, 2011)
A patient operated on at the Department of Urology of the Arnaldo Milian Castro Provincial University Hospital in Santa Clara is presented. The patient had a diagnosis of right renal pelvic calculi and was operated on using a minimally invasive technique implemented for the first time in our province.